Syahirah represents Malaysia in Chinese Bridge Competition - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 18 July 2021 - A student from the Faculty of Computing (FK), Universiti Malaysia Pahang (UMP), Syahirah Syazwani Shamsudin won first place in the Chinese Bridge Competition Malaysia Preliminary 2021 organised by the Chinese Embassy in collaboration with Kongzi Institute, University of Malaya (UM) recently.